ANALISIS PERKEMBANGAN PLTS DI PROVINSI SUMATERA SELATAN MENUJU TARGET 296,6 MW PADA TAHUN 2025 - D.Y. Manurung; I.N.S. Kumara; W.G. Ariastina W.G. Ariastina; J. Pangaribuan (Jurnal SPEKTRUM, 2022)
Target capacity of Solar Power Plant in Province of South Sumatra is pursued throughthe construction of a rooftop PV mini-grid system with off-grid and on-grid systems. Based onNational Energy General Plan (RUEN) in 2017, Province of South Sumatra has the third largestsolar power potential on a national scale with a target of Solar Power Plant developmentreaching 296.6 MW in 2025. Province of South Sumatra is the second most populous provinceon Sumatra Island with electricity consumption reaching 5,308 GWh in 2020. This study tries toanalyze the development of Solar Power Plant in Province of South Sumatra based on theliterature review. Solar Power Plant that has been installed until 2021 reached 12.441 MW oraround 4.12% of the South Sumatra RUEN target of 296.6 MW in 2025. The types of SolarPower Plant applications in Province of South Sumatra consist schools, hotels, palm oilfactories, irrigation pumps , and utility networks spread across Palembang, Muara EnimRegency, Muara Rawas Regency, and Ogan Hilir Regency